2004
DOI: 10.1016/j.ssc.2003.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric photonic crystal as medium with negative electric permittivity and magnetic permeability

Abstract: We show that a two-dimensional photonic crystal (PC) made from a non-magnetic dielectric is a left-handed material in the sense defined by Veselago. Namely, it has negative values of both the electric permittivity ǫ and the magnetic permeability µ in some frequency range. This follows from a recently proven general theorem. The negative values of ǫ and µ are found by a numerical simulation.Using these values we demonstrate the Veselago lens, a unique optical device predicted by Veselago. An approximate analyti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 20 publications
0
36
1
Order By: Relevance
“…Generally, there are several methods to realize a highly directional light source [7][8][9][10][11][12][13][14][15][16][17][18]. A highly directional light source can be obtained, for example, by putting a point source within a resonant cavity structure [7,8], or by placing a point source in a finite photonic crystal [9][10][11], or due to the excitation of surface wave modes [12][13][14], or by utilizing the interference effect from several coherent sources [15,16], or by using electromagnetic wave metamaterials with negative permittivity and permeability [17,18]. Soon, it has also been shown that a highly directional acoustic source can be realized by similar methods [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there are several methods to realize a highly directional light source [7][8][9][10][11][12][13][14][15][16][17][18]. A highly directional light source can be obtained, for example, by putting a point source within a resonant cavity structure [7,8], or by placing a point source in a finite photonic crystal [9][10][11], or due to the excitation of surface wave modes [12][13][14], or by utilizing the interference effect from several coherent sources [15,16], or by using electromagnetic wave metamaterials with negative permittivity and permeability [17,18]. Soon, it has also been shown that a highly directional acoustic source can be realized by similar methods [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Following the definition of negative index materials [4], the first natural way to solve this problem was to split the index into two parameters: the permittivity and the permeability. Also, following the shape of the dispersion law, it is natural to consider an anisotropic homogeneous medium: the permittivity and the permeability are tensors [18][19][20]. Finally, as recently introduced in [21][22][23], we consider permittivity and permeability which can take complex values.…”
Section: Introductionmentioning
confidence: 99%
“…Efros 25 argued that the LHM can not be approximated by a homogeneous system because of the periodicity of the meta-material 17,26 .…”
Section: Introductionmentioning
confidence: 99%